Impacts of Cittaslow Philosophy on Sustainable Tourism Development: Case of North Cyprus - İnce, Ecem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Sustainability concept exists in the soul of the Cittaslow (slow city) philosophy. This protest movement mainly based on the philosophy of sustainability, and also strongly emphasizes to increase residents’ awareness about the concept of slowness and ensure sustainable local development. This research aims to analyze the impact of Cittaslow (slow city) philosophy on sustainable tourism development by considering the perception of local people in North Cyprus. In this context, the resident's support for sustainable tourism development has examined in terms of sustainability dimensions (socio-cultural, economic, and environmental). The quantitative research approach has used to observe the significant effects of Cittaslow philosophy and examine the resident's perception regarding tourism development in this study. The dataset has collected by the researcher applying a stratified random sampling method. Self- administered questionnaires were conducted to residents who are living in slow cities (Yeni Boğaziçi, Mehmetçik, Lefke, Geçitkale, and Tatlısu) in North Cyprus. The partial least squares approach to the structural equation model (PLS-SEM) used to analyze the data. The slow city concept is a very significant movement that emphasizes the importance of local differences and sustainability. In this context, there is not enough knowledge regarding the effects of Cittaslow membership and efforts on sustainable tourism development in North Cyprus. In this study, the research results discussed the important issues in the management of slow cities. Some critical factors, regarding the impacts of tourism, have been found to explain the perception of residents on support for sustainable tourism development. The policies of quality of city life and agricultural, touristic and artisan activities have emerged as a positive perception of the residents; infrastructure policies, energy policies, partnerships, and social cohesion have been found as a negative perception of the residents. Lastly, implications pinpointed for ensuring sustainable tourism development in slow cities. Keywords: Cittaslow (Slow City), Sustainability, Sustainable Tourism Development, North Cyprus, Impacts of Tourism.

ÖZ: Sürdürülebilirlik kavramı, Cittaslow (yavaş şehir) felsefesinin ruhunda bulunmaktadır. Bu protesto hareketi esas olarak sürdürülebilirlik felsefesine dayanmaktadır ve aynı zamanda yerel halkın yavaşlık kavramı hakkındaki farkındalıklarını arttırmayı ve sürdürülebilir yerel kalkınmayı sağlamayı güçlü bir şeklide vurgulamaktadır. Bu araştırma, Cittaslow (yavaş şehir) felsefesinin sürdürülebilir turizm gelişimi üzerindeki etkisini Kuzey Kıbrıs'ta yaşan yerel halkın algısını dikkate alarak analiz etmeyi amaçlamaktadır. Bu bağlamda, yerel halkın sürdürülebilir turizm gelişimine verdiği destek sürdürülebilirlik boyutları (sosyo-kültürel, ekonomik ve çevresel) açısından incelenmiştir. Nicel araştırma yaklaşımı, Cittaslow felsefesinin önemli etkilerini gözlemlemek ve bu çalışmada konut sakinlerinin turizm gelişimi ile ilgili algılarını incelemek için kullanılmıştır. Veri seti, araştırmacı tarafından tabakalı rastgele örnekleme yöntemi kullanılarak toplanmıştır. Kuzey Kıbrıs'ta yer alan yavaş şehirlerde (Yeni Boğaziçi, Mehmetçik, Lefke, Geçitkale ve Tatlısu) yaşamakta olan yerel halk ile yüz yüze anket çalışması yapılmıştır. Verilerin analizinde, yapısal eşitlik modeli (PLS-SEM) kısmi en küçük kareler yaklaşımı kullanılmıştır. Yavaş şehir kavramı, yerel farklılıkların ve sürdürülebilirliğin önemini vurgulayan çok önemli bir harekettir. Bu kapsamda, Cittaslow üyeliği ve çalışmalarının, Kuzey Kıbrıs'ta sürdürülebilir turizm gelişimi üzerindeki etkileri hakkında yeterli bilgi bulunmamaktadır. Araştırma sonuçlarında, yavaş şehirler yönetimindeki önemli konular ve sonuçlar tartışılmıştır. Bu çalışmada, turizmin etkilerine ilişkin bazı kritik faktörlerin, bölge sakinlerinin sürdürülebilir turizm gelişimine destek konusundaki algısını açıkladığı görülmüştür. Kentsel yaşam kalitesi ve tarım, turizm ve zanaat faaliyetleri ile ilgili politikalar bölge sakinlerinin olumlu algısı olarak ortaya çıkmıştır; altyapı politikaları, enerji politikaları, ortaklıklar ve sosyal uyum bölge sakinlerinin olumsuz algısı olarak bulunmuştur. Son olarak, yavaş şehirlerde sürdürülebilir turizm gelişiminin sağlanması için çıkarımlar ortaya konulmuştur. Anahtar Kelimeler: Yavaş Şehir (Sakin Şehir), Sürdürülebilirlik, Sürdürülebilir Turizm Gelişimi, Kuzey Kıbrıs, Turizmin Etkisi.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Co-Supervisor: Prof. Dr. Ali Öztüren, Supervisor: Assoc. Prof. Dr. Deniz İşçioğlu.
Keywords: Tourism; Tourism--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Cittaslow; Cittaslow (Slow City); Sustainability; Sustainable Tourism Development; North Cyprus; Impacts of Tourism